NI-15 THE USEFULNESS OF PET IMAGING IN MOLECULAR DIAGNOSIS OF GLIOMA - Ogawa, Tomoya (Neurooncol Adv, 2019)
OBJECTIVE: After WHO 2016 Classification of Tumors of the Central Nervous System have published, molecular diagnosis became part of the diagnostic criteria. In this study, we investigated the correlation between PET images and molecular diagnosis of glioma. METHODS: We performed retrospective review of newly diagnosed supratentorial glioma patients who preoperatively underwent all four PET examinations ((18)F-FDG, (11)C-MET, (18)F-FLT and (18)F-FMISO) from April 2009 to March 2019. The standardized uptake value (SUV) from the accumulation of each PET tracers, TNR (tumor to contralateral normal tissue ratio) of (18)F-FDG,(11)C-MET and (18)F-FLT, TBR (tumor to blood values ratio) of (18)F-FMISO were measured. We investigated the correlation between these PET images and molecular diagnosis of glioma. RESULTS: Data from total of 79 patients which were 42 cases of IDH wild type glioblastoma, 2 cases of IDH mutated glioblastoma, 9 cases of IDH wild type astrocytoma, 13 cases of IDH mutated astrocytoma and 13 cases of IDH mutated and 1p/19q co-deleted oligodendroglioma were included in this study. Both TNR of (11)C-MET(p<0.01) and (18)F-FLT(p<0.01), and also TBR of (18)F-FMISO(p<0.01) in IDH wild type gliomas showed significantly higher than IDH mutated gliomas. In WHO Gr2-3 gliomas, only TNR of (18)F-FLT showed a significant difference between IDH wild type gliomas and IDH mutated gliomas(p<0.01). TNR of (18)F-FLT(p<0.01) and TBR of (18)F-FMISO(p<0.01) in 1p/19q co-deleted gliomas were significantly lower than gliomas without 1p/19q co-deletion, but there were no significant differences in WHO Gr2-3 gliomas. Among IDH mutated gliomas, TNR of (11)C-MET in 1p/19q co-deleted gliomas showed significantly higher uptake than gliomas without 1p/19q co-deletion(p<0.05). CONCLUSION: Preoperative PET evaluation of each PET tracers may be useful for the molecular diagnosis of glioma.